The Principle of State Sovereignty and Its Limitations under Contemporary International Law: Implications for Indonesia's Foreign Policy and Regional Cooperation - Erni Yoesry; Nur Annisa Putri; Evi Selviani; Elmiati Nurdin; Nur Ilmi Putri Febriyanti (CV. Era Digital Nusantara, 2026)
This study aims to analyze the principle of state sovereignty and its limitations in the context of international law, along with its implications for Indonesian foreign policy. This study will be conducted using a qualitative research approach, relying on normative legal research methods and utilizing secondary data from various international legal instruments, academic literature, and relevant policy documents. The study's findings highlight the importance of the principle of sovereignty in international relations, yet its implementation is often subject to various constraints within the context of international law, including international commitments in the areas of human rights, environmental protection, global security, and international cooperation. For Indonesia, the evolving interpretation of sovereignty requires a strategic balance between maintaining national autonomy and fulfilling international responsibilities. Indonesia's active engagement in regional frameworks, particularly within ASEAN, reflects an adaptive foreign policy approach that seeks to uphold sovereignty while promoting regional stability and cooperation.